EMBLEM S-ICDr System Cardioversor Desfibrilador Implantável Subcutâneo: EMBLEM S-ICDr System Cardioversor Desfibrilador Implantável Subcutâneo - Scientific, Boston (JOURNAL OF CARDIAC ARRHYTHMIAS, 2017)
Espaço publicitário